Implementing a pharmacist-led, individualized medication assessment and planning (iMAP) intervention to reduce medication related problems among older adults with cancer. Issue 4 (July 2017) - Nightingale, Ginah; Hajjar, Emily; Pizzi, Laura T.; Wang, Margaret; Pigott, Elizabeth; Doherty, Shannon; Prioli, Katherine M.; Swartz, Kristine; Chapman, Andrew E.
Abstract: Objectives: Medication-related problems (MRP) affecting older adults are a significant healthcare concern and account for billions in medication-related morbidity. Cancer therapies can increase the prevalence of MRP. The objective of this study was to test the feasibility and effectiveness of implementing a pharmacist-led individualized medication assessment and planning (iMAP) intervention on the number and prevalence of MRP. Materials and Methods: This prospective pilot study enrolled oncology outpatients aged ≥ 65 years. Intervention feasibility encompassed recommendation acceptance rate and intervention delivery time. The intervention was facilitated by pharmacists where patients received comprehensive medication management at baseline and at the 30- and 60-day follow-up. Results: Forty-eight eligible patients enrolled and 41 patients (85.4%) were included in the analysis. Mean age was 79.1 years [range 65–101]; 66% women, 83% Caucasian, mean comorbidity count was 7.76. Forty-six percent of the pharmacist recommendations were accepted and the prevalence of MRP at baseline versus 60-day follow-up decreased by 20.5%. The average time to conduct the initial session was 22 min versus 15 min for the follow-up sessions. Resources needed included a tracking system for scheduling follow-up calls and a database for tracking acceptance of recommendations. A total of 123 MRP were identified in 95% of patients (N = 39) with a mean of 3 MRP per patient. The mean reduction in number of MRP (3 at baseline versus 1.6 at 60-day follow-up) was 45.5%. Conclusions: The pharmacist-led iMAP intervention was feasible and effective at reducing MRP. Additional inter-professional medication safety based interventions measuring patient-reported outcomes are still needed.